PENATAAN KAWASAN PEMUKIMAN BANTARAN SUNGAI DESA GALUMPANG KABUPATEN TOLITOLI (STUDI KASUS:DUSUN KUALA RT. 1 dan RT. 2) - Mansur S Pahude, (Journal of Innovation Research and Knowledge, 2024)
The residential area on the riverbank of Galumpang Village has an important role in the lives of the people in the area. However, the arrangement of residential areas that do not pay attention to environmental aspects can also cause river degradation, uncontrolled human activities, such as the discharge of domestic and industrial waste into rivers, resulting in river water pollution which has a negative impact on public health and the sustainability of the river ecosystem itself. The aim of the riverbank in Galumpang Village, Tolitoli Regency is to create a housing design that is able to adapt to the environment, such as riverbanks which are prone to flooding by handling and rearranging the riverbank settlements in Galumpang Village, Dusun Kuala RT. 1 and RT. 2 as well as providing alternative housing designs that are safe from floods or river overflows. The arrangement of riverbank settlements in Galumpang Village, Tolitoli Regency is designed with a riverfront concept, where in planning the area is located on the riverbank and has buildings that face directly towards the river, and is bordered by green belts or green open spaces in accordance with border lines and protected areas. local.